Solution To The Implementation Of Zakat As A Deduction From Income Tax Payable (Taxes Credit) In Aceh Province - M Yasir Nasution; Saparuddin Siregar; Ngatno Syahputra (Proceeding International Seminar of Islamic Studies, 2019)
: Zakat as a deduction from the income tax payable (Credit Taxes) in Aceh Province This study aimed to m e ndapatka n empirical evidence of the Solution Implementation of zakat as a deduction from the income tax payable (Credit Taxes) in the province of Aceh . This study uses qualitative methods with ANP ( Analytic Network Process ) analysis tools . The results of the study explains that problem most priorities that need to quickly get the response is in the form of government aspect. Implementation is the most priority Baitul Maal problem. Prior problems itas faced by pemerint ah that is related to the position between zak a t and taxes . Baitul maal solution with the most priority is to carry out the mandate of the Constitution and the solution for the most priority government is equal, where both zakat and tax must be the same. Conclution of how it is that charity as a deduction from the income tax payable in the province of Aceh has not been implemented because the government has not dared to issue related PP BAL and there is disharmony between the income tax law with the Law